Associations of CYP2C9 and CYP2C19 Pharmacogenetic Variation with Phenytoin‐Induced Cutaneous Adverse Drug Reactions - Alison E. Fohner; Allan E. Rettie; Khanh K. Thai; Dilrini K. Ranatunga; Brian L. Lawson; Vincent X. Liu; Catherine A. Schaefer (Wiley, 2020)
The role of cytochrome P450 (CYP)2C9 and CYP2C19 genetic variation in risk for phenytoin‐induced cutaneous adverse drug events is not well understood independently of the human leukocyte antigen B (HLA‐B)*15:02 risk allele. In the multi‐ethnic resource for Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort, we identified 382 participants who filled a phenytoin prescription between 2005 and 2017. These participants included 21 people (5%) who self‐identified as Asian, 18 (5%) as black, 29 (8%) as white Hispanic, and 308 (81%) as white non‐Hispanic. We identified 264 (69%) CYP2C9*1/*1, 77 (20%) CYP2C9*1/*2, and 29 (8%) CYP2C9*1/*3. We also determined CYP2C19 genotypes, including 112 with the increased activity CYP2C19*17 allele. Using electronic clinical notes, we identified 32 participants (8%) with phenytoin‐induced cutaneous adverse events recorded within 100 days of first phenytoin dispensing. Adjusting for age, sex, daily dose, and race/ethnicity, participants with CYP2C9*1/*3 or CYP2C9*2/*2 genotypes were more likely to develop cutaneous adverse events compared with CYP2C9*1/*1 participants (odds ratio 4.47; 95% confidence interval 1.64-11.69; P < 0.01). Among participants with low‐intermediate and poor CYP2C9 metabolizer genotypes, eight (22%) who also had extensive and rapid CYP2C19 metabolizer genotypes experienced cutaneous adverse events, compared with none of those who also had intermediate CYP2C19 metabolizer genotypes (P = 0.17). Genetic variation reducing CYP2C9 metabolic activity may increase risk for phenytoin‐induced cutaneous adverse events in the absence of the HLA‐B*15:02 risk allele.